Assessment of market risk in banking as one of the risk pillars in enterprise risk management - Rabie, Nancy Ashraf (AUC Knowledge Fountain, 2020)
The global financial crisis of 2007-2008 uncovered the weakness of the risk management in the banking sector. Failure of the banking risk management was due to the unforeseen risks not accounted for in banks’ risk management systems, along with weak supervisory monitoring. As a result, Basel Accords had undergone a series of improvement to stress the importance of looking at different risks in an integrated approach, which marked the beginning of a new era for risk management. Banks started to move towards implementing a holistic approach in managing risk, a dynamic approach, which is Enterprise Risk Management (ERM). ERM is managing risks of an entity under a holistic approach instead of the current silo approach. Assessing risk under the umbrella of ERM ensures that banks are measuring risks using all possible approaches to optimize their economic capital and hold the correct required regulatory capital . Moreover, it captures the interdependence between risks, which enhances risk measures. The financial crisis highlighted the importance of market risk and how it interacts with other risks facing financial institutions. Market risk is the losses incurred in on and off-balance sheet items affected by changes in market prices, such as, interest rates and foreign exchange. This paper objective is to measure market risk as a standalone risk using different approaches of both traditional Value at Risk (VaR) and Expected Shortfall (ES) for banks in Europe, Asia and Africa regions to calculate the banks required regulatory capital according to Basel using Value at Risk (VaR) and Expected Shortfall (ES). Finally, the results would aid each region’s banks in determining its exposure to market risk. These results should be used as one of the components of the ERM approach to calculate the aggregate risk exposure after integration with other risks.